2016
DOI: 10.3897/compcytogen.v10i1.5699
|View full text |Cite
|
Sign up to set email alerts
|

Identification of homogeneously staining regions by G-banding and chromosome microdissection, and FISH marker selection using human Alu sequence primers in a scleractinian coral Coelastrea aspera Verrill, 1866 (Cnidaria)

Abstract: Karyotype analysis was performed on the scleractinian coral Coelastrea aspera Verrill, 1866, commonly found along temperate coasts in Japan (30–35°N) and in coastal waters in the Indian and Pacific oceans. G-banding of Coelastrea aspera was successfully performed, although the banding pattern was not as clear as that in mammals. The karyogram clearly revealed that this coral had a (hsr)homogeneously staining region in chromosome 11. This hsr consisted of (rRNA)ribosomal RNA related genes, which was demonstra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
16
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 8 publications
(19 citation statements)
references
References 22 publications
3
16
0
Order By: Relevance
“…As a result of G-and C-banding analyses, we identified an hsr on P. contorta chromosome 12 after karyotyping. An hsr has been found previously in the corals C. aspera and E. aspera (Taguchi et al 2013(Taguchi et al , 2016. Conventional Cbanding revealed that the hsr portion of P. contorta was C-band positive (darkly stained), indicating the presence of specific proteins, such as centromere regions.…”
supporting
confidence: 52%
See 3 more Smart Citations
“…As a result of G-and C-banding analyses, we identified an hsr on P. contorta chromosome 12 after karyotyping. An hsr has been found previously in the corals C. aspera and E. aspera (Taguchi et al 2013(Taguchi et al , 2016. Conventional Cbanding revealed that the hsr portion of P. contorta was C-band positive (darkly stained), indicating the presence of specific proteins, such as centromere regions.…”
supporting
confidence: 52%
“…To solve the controversial taxonomic issue (Fukami et al 2004) and develop an understanding of coral genetics, we have been accumulating molecular cytogenetic data of scleractinian corals. So far, we have published three molecular cytogenetic reports using FISH on scleractinian corals, such as A. solitaryensis, E. aspera, and C. aspera (Taguchi et al 2013(Taguchi et al , 2014(Taguchi et al , 2016, which are commonly found on the western coast of Japan (Wallace 1999). The present study is our fourth report and concerns P. contorta; it is a different genus from our previous studies but is classified in the same family Merulinidae with C. aspera.…”
Section: Discussionmentioning
confidence: 60%
See 2 more Smart Citations
“…Besides these contradictory data, molecular cytogenetic approaches like (FISH)florescence in situ hybridization have not been applied in this species yet. Such methods being available since the late 1980s (Li et al 2016, Taguchi et al 2016) enable detection, characterization and localization of rDNA regions (Chirino et al 2015) and/or telomeres. The latter are known to be important to protect chromosomal ends of all eukaryotes against nucleolytic degradation, non-homologous end-joining and replication-mediated shortening.…”
Section: Introductionmentioning
confidence: 99%